The Routledge introduction to American comics - Kunka, Andrew, 1969- author. Link
1 online resource.
Keywords: "This accessible, up-to-date textbook covers the history of comics as it developed in the U.S. in all of its forms: political cartoons and newspaper comic strips, comic books, graphic novels, minicomics, and webcomics. Over the course of its five chapters, this introductory textbook addresses the artistic, cultural, social, economic, and technological impacts and innovations that comics has had in American history. Readers will be immersed in the history of American comics - from its origins in 18th century political cartoons and late 19th century newspaper strips to the rise of the wildly popular comic book, the radical, grassroots collectives that grew out of the underground comix movement of the 1960s and 70s, all the way through contemporary longform graphic novels, the vibrant self-publishing scene, and groundbreaking webcomics. The Routledge Introduction to American Comics guides students, researchers, archivists, and even fans of the medium through a contemporary history of comics, attending to how a diverse range of creators and researchers have advanced the art form in key ways since its inception as a foundational art of American popular culture. In this way, it is uniquely suited for readers engaged in the study of comics as well as those interested in the creation of comics and graphic narratives"--